Radical democracy and political theology - Robbins, Jeffrey W. (Insurrections, 2011)
Democracy, more or less -- Interlude : managing democracy abroad -- Democracy, radically conceived -- Political theology and the postsecular -- Interlude : the Iranian Revolution redux -- Political theology, beyond despair -- Political theologies, or finding an alternative to Schmitt -- The theopolitics of democracy -- Interlude: the messianic as a democratic political theology -- Conclusion : from the one to the many